A portrait of the artist as a young man - Joyce, James (AITBS Publishers London, 2018)
"A Portrait of the Artist as a Young Man" is a semi-autobiographical novel by James Joyce, chronicling the intellectual and emotional development of Stephen Dedalus, a young man growing up in late 19th-century Ireland. Through a stream-of-consciousness narrative, Joyce explores themes of religion, identity, rebellion, and artistic awakening. Stephen struggles with the constraints of family, society, and the Catholic Church, ultimately rejecting them in his quest for self-expression and artistic freedom. The novel captures the psychological growth of its protagonist, illustrating his journey toward becoming an independent artist. 4o Is this conversation helpful so far?